Intensification of Sonophotocatalytic Degradation of Ponceau S using Fe - Doped and Undoped ZnO Nano Catalyst - Mahajan, V. K.; Shelar, S. G.; Patil, S. P.; Sonawane, G. H. (Journal of Scientific Research, 2024)
Fe-doped ZnO nano catalyst was synthesized by co-precipitation method. The intrinsic characteristics of a prepared nano Fe-doped ZnO catalyst were studied using a variety of techniques including powder X-ray diffraction (XRD), scanning electron microscope (SEM), electron dispersive X-ray spectroscopy (EDS). In this study, degradation of Ponceau S as a dye pollutant was investigated in the presence of ZnO and Fe-doped ZnO nano catalyst using sonolysis, photocatalysis, sonocatalysis and sonophotocatalysis. The UV light and ultrasonic probsonicator at 20 kHz and 150 W powers were used as an irradiation source. The effect of H2O2 on sonocatalytic, photocatalytic and sonophotocatalytic degradation was investigated. At optimum conditions the dye degradation efficiency was influenced by addition of H2O2, the highest dye degradation was obtained as 98 % by US+UV+Fe-doped ZnO+H2O2 for 40 mg/L dye concentration after 90min. The experimental kinetic data followed the pseudo-first order model in doped and undoped sonocatalytic, photocatalytic and sonophotocatalytic processes but the rate constant of sonophotocatalysis is higher than sonocatalysis and photocatalysis process. The sonophotocatalysis was always faster than the respective individual processes due to the more formation of reactive radicals as well as the increase of the active surface area of nano catalyst.